Risk of bleeding after percutaneous coronary intervention and its impact on further adverse events in clinical trial participants with comorbid peripheral arterial disease. (1st March 2023) - Pinxterhuis, Tineke H.; Ploumen, Eline H.; Zocca, Paolo; Doggen, Carine J.M.; Schotborgh, Carl E.; Anthonio, Rutger L.; Roguin, Ariel; Danse, Peter W.; Benit, Edouard; Aminian, Adel; Stoel, Martin G.; Linssen, Gerard C.M.; et al.
Abstract: Background: Both patients with obstructive coronary artery disease (CAD) and patients with peripheral arterial disease (PADs) have an increased bleeding risk. Information is scarce on bleeding in CAD patients, treated with percutaneous coronary intervention (PCI), who have comorbid PADs. We assessed whether PCI patients with PADs have a higher bleeding risk than PCI patients without PADs. Furthermore, in PCI patients with PADs we evaluated the extent by which bleeding increased the risk of further adverse events. Methods: Three-year pooled patient-level data of two randomized PCI trials (BIO-RESORT, BIONYX) with drug-eluting stents were analyzed to assess mortality and the composite endpoint major adverse cardiac events (MACE: all-cause mortality, any myocardial infarction, emergent coronary artery bypass surgery, or target lesion revascularization). Results: Among 5989 all-comer patients, followed for 3 years, bleeding occurred in 7.7% (34/440) with comorbid PADs and 5.0% (279/5549) without PADs (HR: 1.59, 95%CI: 1.11–2.23, p  = 0.010). Of all PADs patients, those with a bleeding had significantly higher rates of all-cause mortality (HR: 4.70, 95%CI: 2.37–9.33, p  < 0.001) and MACE (HR: 2.39, 95%CI: 1.23–4.31, p  = 0.003). Furthermore, PADs patients with a bleeding were older (74.4 ± 6.9 vs. 67.4 ± 9.5, p < 0.001). After correction for age and other potential confounders, bleeding remained independently associated with all-cause mortality (adj.HR: 2.97, 95%CI: 1.37–6.43, p  = 0.006) while the relation of bleeding with MACE became borderline non-significant (adj.HR: 1.85, 95%CI: 0.97–3.55, p  = 0.06). Conclusion: PCI patients with PADs had a higher bleeding risk than PCI patients without PADs. In PADs patients, bleeding was associated with all-cause mortality, even after adjustment for potential confounders. Graphical abstract: Patients with peripheral arterial disease and any bleeding during 3-year follow-up after percutaneous coronary intervention . Baseline characteristics of patients with peripheral arterial disease with or without a bleeding. Kaplan-Meier cumulative event curves for: (A) major adverse cardiovascular events (B), all-cause mortality (C), and target vessel related myocardial infarction. Patients with peripheral arterial disease with (red) or without (blue) a bleeding. Abbreviations: CI=confidence interval; HR=hazard ratio. Unlabelled Image Highlights: Peripheral arterial disease is confirmed as a serious comorbidity in PCI patients. PCI patients with peripheral arterial disease had a higher bleeding risk. Patients with peripheral arterial disease and bleeding had a higher mortality risk.